The Practice of policy evaluation - Nachmias, David (New York : St. Martin's Press, 1980)
This book introduced students and professionals to research that has been done in policy evaluation. It contains twenty-one policy evaluation studies of domestic topics that are currently major concerns of policymakers and the attentive publics.
Includes bibliographical references.
hza 22/06/2018; 10/07/2018
Loans
Keywords: Evaluation research (Social action programs).; United States